Spesifikasi Kertas Karton Gelombang (KKG) Untuk Kemasan B3 (Bahan Berbahaya Dan Beracun) - Budi Utami (Jurnal Kimia dan Kemasan, 1997)
Dangerous goods should be packaged in good quality of packaging which should be constructed and closed to prevent any leakage which might be caused under normal conditions during transportation. Corrugated .fibreboard boxes which used as secondary packaging, should be adequately strong and water - resistant. The packaging should conform with design type and completely tested in accordance with the requirements of the standard.